Computerized ellipse method for measuring acetabular version after total hip replacement – a precision study using synthetic and real radiographs. (10th May 2013) - Liaw, Chen-Kun; Wu, Tai-Yin; Hou, Sheng-Mou; Yang, Rong-Sen; Shih, Kao-Shang; Fuh, Chiou-Shann
Abstract : Background: Previous work by our group to address the problem of acetabular positioning based on 2D methods resulted in the development of a measurement method with better precision – Liaw's version. This method may help the early diagnosis of acetabular loosening. In the present study, we hypothesized that our computerized ellipse method could improve the precision of measuring acetabular version. Methods: We developed our Elliversion software to measure acetabular version. Using total hip replacement (THR) Simulator, 96 radiographs were synthesized with random femoral inclination and 5° to 52° version, half with the femoral head included and half without. These synthetic radiographs and 28 real radiographs were measured with both Elliversion and the trigonometric method twice by one of the authors with a one-week interval between measurements. We then calculated the difference in the repeated measurements. Student's t -test was used for statistical analysis of the measuring error and inter-measurement difference. Results: In the precision study, for synthetic radiographs including the femoral head, the ellipse method was significantly better than the trigonometric method ( p < 0.01). For synthetic radiographs without the femoral head, there was no significant difference between the ellipse method and the trigonometric method ( p = 0.19). As for the repeated measurements, for synthetic radiographs including the femoral head, the ellipse method was significantly better than the trigonometric method ( p = 0.001), whereas for synthetic radiographs without the femoral head, there was no significant difference between the two methods ( p = 0.17). For real radiographs, there was no significant difference between the two measuring methods ( p = 0.12). However, if we excluded the four poor-quality radiographs, there was a significant difference between the two measuring methods ( p = 0.04). Discussion: We developed a computerized ellipse method for measuring acetabular version on synthetic radiographs and good-quality real radiographs. This method is characterized by its superior precision as compared to the trigonometric method. With the 2D standardized method (Liaw's version), improving the precision of measurement will help earlier diagnosis of acetabular loosening.